Aspectos da política fiscal no primeiro governo Dilma Rousseff (2011-14) e os efeitos no desempenho econômico brasileiro no período - Garritano, César (2019)
This dissertation aims to analyze fiscal policy decisions and their effects on the performance of the Brazilian economy in the first term of President Dilma Rousseff's government (2011-2014). Through the support of John Maynard Keynes's theory regarding the state's performance in the economy through fiscal policy, the intention is to analyze and point out that the choice of the President Dilma Rousseff government to privilege tax exemptions to the detriment of investments, a predilection that represented a change from what had been practiced by the previous government, was a key factor for the deterioration of the Brazilian economy in the first four years of the current decade. In order to better understand the possibilities and the decisions in the first President government, this dissertation also approach the historical background government of the former presidents Fernando Henrique Cardoso and Luiz Inácio Lula da Silva, concerning the economic, political and international scenarios